Enhancing public engagement through NICU storytelling on Facebook and Instagram: a case study from Gaslini Children’s Hospital - Canepa, Maria E.; Macciò, Maura; Raffini, Luca; Striano, Pasquale; Ramenghi, Luca A. (Frontiers in Communication, 2024)
Background: Social media platforms, particularly Instagram, have become pivotal in disseminating medical information to the public. However, the challenge of presenting neonatal intensive care unit PAGE \* Arabic \* (NICU) stories in a manner that is both engaging and informative remains significant, especially in the context of a reputable pediatric hospital. Objective: This study aims to explore the effectiveness of Instagram as a storytelling medium for NICU experiences at the Gaslini Children's Hospital, focusing on the impact of various storytelling elements on audience engagement and follower growth. Methods: We analyzed Facebook and Instagram posts of the Gaslini Children's Hospital, examining factors such as emotional appeal, news value, and content quality. Additionally, we considered the adherence of these posts to journalistic and medical guidelines. Results: The research identified key themes in successful posts, including emotional resonance, portrayal of medical excellence, and humanization of patient stories. Posts that effectively combined these elements saw significant increase in audience engagement, including likes, comments, and shares. Conclusion:Strategic storytelling on Instagram can significantly enhance public engagement with hospital content, fostering a deeper connection between the institution and its audience. This study underscores the significance of narrative elements and adherence to ethical guidelines in crafting compelling medical stories for social media.